IMPLEMENTASI PEMILIHAN JENIS PAKAN TERNAK TERBAIK MENGGUNAKAN METODE VIKOR - Efa Arfin Lauda; Saifur Rohman Cholil (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
This study applies the VIKOR method in determining the best type of animal feed to support the productivity of laying hens. This method is used to analyze and rank various feed alternatives based on a number of important criteria, such as nutritional quality, cost efficiency, and sustainability. Data collection was carried out through direct interviews with farmers and direct observations in the field. The analysis was carried out using a multicriteria approach with weights determined based on the level of importance of each criterion. The results of the study showed that alternative A7 (fish meal) with a Q value = 0.000 ranked highest as the most optimal type of animal feed. This shows that fish meal has the best balance in meeting the various criteria that have been set. Conversely, alternative A9 (table salt) with a Q value = 1.000 ranked lowest, reflecting its least optimal performance. The VIKOR method has proven effective in providing a balanced compromise solution, so that farmers can make more accurate and data-based decisions. The application of the VIKOR method in the selection of animal feed provides significant benefits in increasing livestock efficiency and productivity. In addition, this approach also supports more sustainable and competitive livestock management, so that it has the potential to be adopted more widely in the livestock sector.